2020
DOI: 10.3892/ol.2020.11988
|View full text |Cite
|
Sign up to set email alerts
|

Low HOXC10 expression in liver cancer regulates proliferation via a mechanism involving miR‑221 and the MAPK signaling pathway

Abstract: Homeodomain-containing gene 10 (HOXC10) is associated with the progression of a variety of different types of human cancer; however, the role of HOXC10 in liver cancer is not completely understood. The present study aimed to investigate the mechanisms underlying the effects of HOXC10 on liver cancer tumorigenesis. Quantitative PCR and western blotting were used to detect the expression patterns of HOXC10 in cancer and adjacent healthy tissues. EdU, Cell Counting Kit-8 and colony formation assays were used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Conversely, Ma et al. ( 61 ) found that HOXC10 have negatively affected the MAPK signaling pathway, and MAPK signaling marker proteins increase significantly after HOXC10 knockdown in liver cells. This suggests that HOXC10 has diverse effects on the MAPK pathway in different tumors.…”
Section: Tumorigenesismentioning
confidence: 96%
See 2 more Smart Citations
“…Conversely, Ma et al. ( 61 ) found that HOXC10 have negatively affected the MAPK signaling pathway, and MAPK signaling marker proteins increase significantly after HOXC10 knockdown in liver cells. This suggests that HOXC10 has diverse effects on the MAPK pathway in different tumors.…”
Section: Tumorigenesismentioning
confidence: 96%
“…We also provided a comprehensive description of HOXC10 expression regulation. Specifically, HOXC10 expression is regulated by several epigenetic processes, including DNA ( 6 , 50 , 96 ) and histone ( 5 , 97 ) methylation, posttranscriptional miRNA ( 10 12 , 59 , 61 , 64 , 98 ) and lncRNA ( 9 , 99 ) modifications, and ubiquitin modifications ( 100 ).…”
Section: Hoxc10 Expression Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant changes in the ratio of vitamin intake were found to affect the CpG island methylation pattern in the loci of DNMT1, DNMT3A and DNMT3B, consequently leading to increased expression of the methyltransferases [ 29 ]. Even levels of miRNAs like that of miR-133 (linked to muscle and cardiac tissue metabolism and certain kinds of cancer) [ 54 , 58 , 65 , 85 , 86 , 98 , 101 ] and miR-221 (linked to oncogenesis) [ 10 , 25 , 50 , 56 , 60 , 71 , 79 , 90 , 96 , 100 ] changed in response to a skewed ratio of intake of the two vitamins. Other than sub or supra-optimal levels of folate or B12 intake, vitamin C or ascorbic acid consumption during the perinatal period also seems significant [ 19 ].…”
Section: Maternal Dietary and Supplementary Intakesmentioning
confidence: 99%
“…The Hox gene family consists of 39 genes divided into 4 clusters ( HOXA, HOXB, HOXC , and HOXD ) ( Cillo et al., 2001 ) located on 4 different chromosomes; the HOXC6 and HOXC10 genes are members of the HOXC cluster. The related research on HOXC6 and HOXC10 has been conducted mainly in the context of cancer ( Dang et al., 2020 ), cell proliferation and migration ( Kim et al., 2019 ; Ma et al., 2020 ), neural development ( Wu et al., 2008 ), and adipose tissue browning ( Ng et al., 2017 ). There is no research indicating that HOXC6 and HOXC10 are related to the formation of crested phenotype.…”
Section: Discussionmentioning
confidence: 99%